2006
DOI: 10.1159/000097046
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombotic Therapy and Predilection for Cerebellar Hemorrhage

Abstract: Background: With the recent increase in the use of antithrombotic therapy, intracerebral hemorrhage (ICH) has been found to be a common complication. We determined whether the use of oral antithrombotic therapy and the patients’ preexisting comorbidities were predictive of cerebellar hemorrhage (CH; previously reported to be associated with anticoagulants) as compared to other ICH, and whether antithrombotic therapy affected the clinical severity of CH. Methods: A study of 327 consecutive patients hospitalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 40 publications
(27 reference statements)
3
14
2
Order By: Relevance
“…The in-hospital mortality of 21.4% observed in our patients [5] is lower than 39-47% observed in other studies [22][23][24] and similar to death rates (13% and 25%) reported by other authors [25,26]. Patients with larger cerebellar hematomas ussually develop brainstem compression [25,28].…”
Section: Cerebellar Hemorrhagesupporting
confidence: 83%
“…The in-hospital mortality of 21.4% observed in our patients [5] is lower than 39-47% observed in other studies [22][23][24] and similar to death rates (13% and 25%) reported by other authors [25,26]. Patients with larger cerebellar hematomas ussually develop brainstem compression [25,28].…”
Section: Cerebellar Hemorrhagesupporting
confidence: 83%
“…The present study showed that there was a strong relationship between cerebellar hemorrhage and any type of antithrombotic therapy, including antiplatelet medication. This result is clearer than our previous one [28], partly because the larger population reduced statistical errors. However, the mechanism that explains why antithrombotic therapy triggers cerebellar hemorrhage remains unknown.…”
Section: Discussionsupporting
confidence: 42%
“…In our previous study involving 327 ICH patients [28], warfarin therapy with an INR >2.5 was associated with an excess of cerebellar hemorrhage. A study from Hong Kong showed that there was a predilection for lobar hemorrhage among aspirin users [29], while other studies did not show this [7, 8].…”
Section: Discussionmentioning
confidence: 99%
“…The most common location of hematoma was the thalamus in the OA group, and putaminal hemorrhage was less than in non OA group. This phenomenon was similar to previous studies (12,27). In the OA group, thalamus or basal ganglia were the common location of supratentorial hemor- (15).…”
Section: Discussionsupporting
confidence: 92%
“…Table 2 shows vital signs, CT findings, outcome, and laboratory data. GCS was lower in the OA group than in the non-OA group (median 10 [25th-75th percentile: 5-14] vs., 13 [10][11][12][13][14][15], p<0.001). The OA group had larger hematoma [median 22 mL (25th-75th percentile: 7.2-100 mL), vs. median 14 mL (7-42 mL), p<0.001].…”
Section: Resultsmentioning
confidence: 97%